2011
DOI: 10.1002/humu.21652
|View full text |Cite
|
Sign up to set email alerts
|

CDH13 gene coding t-cadherin influences variations in plasma adiponectin levels in the Japanese population

Abstract: Adiponectin is most abundantly expressed in adipose tissue and well known to play an important role in metabolic regulation. Several studies have attempted to identify the genetic determinants of metabolic syndrome (MetS), though no study has revealed a cis- or trans-single nucleotide polymorphism (SNP) that affects plasma adiponectin levels, except the adiponectin structure gene and genes encoding adiponectin-regulatory proteins. We performed a genome-wide association study in regards to plasma adiponectin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 29 publications
(29 reference statements)
6
66
1
Order By: Relevance
“…Tested alleles were defined as previously identified adiponectin-inducing alleles 9, [12][13][14][15] . Multiple linear regression analyses were performed to test the independent effects of each allele from each SNP on adiponectin and metabolic syndrome traits, accounting for the effects of other variables [i.e., age, sex, body mass index (BMI), VFA, and SFA].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tested alleles were defined as previously identified adiponectin-inducing alleles 9, [12][13][14][15] . Multiple linear regression analyses were performed to test the independent effects of each allele from each SNP on adiponectin and metabolic syndrome traits, accounting for the effects of other variables [i.e., age, sex, body mass index (BMI), VFA, and SFA].…”
Section: Discussionmentioning
confidence: 99%
“…We selected three SNPs (rs3865188, rs4783244, and rs12051272) in the CDH13 gene that were recently identified by GWASs 9, [12][13][14][15] and constructed Invader probes (Third Wave Technologies, Madison, WI, USA) for these SNPs. The SNPs were genotyped using Invader assays, as previously described 23) , and used for analysis.…”
Section: Dna Extraction and Single Nucleotide Polymorphism (Snp) Genomentioning
confidence: 99%
See 1 more Smart Citation
“…The CDH13 gene encodes T-cadherin, a receptor for hexameric and high-molecular weight forms of adiponectin (HMWA) (16). Although earlier studies (17,18) and recent GWAS in European subjects (19,20) reported a strong susceptibility of SNPs in the ADIPOQ gene that encodes adiponectin, GWAS of adiponectin in East Asian subjects, namely Korean (15) and Japanese (21), identified SNPs in the CDH13 locus, such as rs4783244.…”
mentioning
confidence: 99%
“…The association of SNPs in the CDH13 locus with plasma adiponectin levels was supported by further studies showing several signals depending on the investigated population, mainly Chinese and Japanese ( Table 2) [134][135][136][137]. The CDH13 promotor SNP rs12444338 G-allele was associated with increased promoter activity in a luciferase assay [134].…”
Section: Adiponectin Receptor 1 and 2 (Adipor1 Adipor2) Cadherin 13mentioning
confidence: 71%